Climing Up, Thinking With, Feeling Through: Ritual, Spirituality and Ecoscience in Northwestern Nepal - Jag Bahadur Budha; Maya Daurio; Mark Turin (Religions)
This paper examines local knowledge, perceptions, and responses to changing climes in the Trans-Himalayan region of Dolpa in Nepal. Rooted within the environmental humanities and shaped by emerging understandings of faith-based ecospirituality, our research partnership focuses on the experiences of the indigenous Tarali Magar people of Gumbatara and neighbouring Shaharatara in the Tichurong valley. Through place-based engagements and drawing on various disciplinary threads and intellectual traditions, we review the effects of changing cultural, climatic, and ritual patterns on the lives and livelihoods of the Tarali Magar community. We explore how (i) agricultural practices are changing and adapting in response to wider systemic transformations; (ii) in what ways physical changes in the weather, clime and climate are experienced and imagined by Taralis through the lens of the Tarali concepts of nham (weather) and sameu (time); and (iii) local knowledge and embodied understandings about the natural and cultural worlds are embedded within Tarali spiritual traditions and religious worldviews. In reckoning with shifts in ecological patterns that disrupt long-standing agricultural practices and the cultural and religious knowledge systems that guide them, we demonstrate that Taralis are indigenous environmental humanists and empirical scientists. Through our study, we uplift culturally grounded, location-specific religious practices in the Tichurong valley and show how members of the Tarali community are contributing to global imaginaries for sustainable futures in our more-than-human world.